2022
DOI: 10.1097/tp.0000000000004261
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Effectiveness of SARS-CoV-2 Vaccination in Renal Transplant Recipients. Antibody Levels Impact in Pneumonia and Death

Abstract: Background. Few studies have described the clinical impact of anti–severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccines in renal transplant recipients (RTRs) in the context of omicron variant and the third vaccine dose. Antibody titer has been tried to relate to the prediction of outcomes related to SARS-CoV-2, but it results controversially in these populations. Methods. All patients with positive SARS-CoV-2 polymerase chain reaction followed at a RTRs reference center from March 15, 2020, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…However, conflicting results were reported specifically in KTRs, which is a vulnerable patient group at high risk of adverse outcomes after SARS-CoV-2 infection. Several studies demonstrated lower immunogenicity after COVID-19 vaccination [ 4 , 26 , 27 , 28 , 29 , 30 ], but only a few studies investigated whether vaccination is effective in lowering COVID-19 incidence and severity in KTRs [ 31 , 32 ]. Hamm et al [ 33 ] showed the protective effects of COVID-19 vaccination in a national registry study from Denmark that included 1428 solid organ transplant recipients, of whom the majority were KTRs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, conflicting results were reported specifically in KTRs, which is a vulnerable patient group at high risk of adverse outcomes after SARS-CoV-2 infection. Several studies demonstrated lower immunogenicity after COVID-19 vaccination [ 4 , 26 , 27 , 28 , 29 , 30 ], but only a few studies investigated whether vaccination is effective in lowering COVID-19 incidence and severity in KTRs [ 31 , 32 ]. Hamm et al [ 33 ] showed the protective effects of COVID-19 vaccination in a national registry study from Denmark that included 1428 solid organ transplant recipients, of whom the majority were KTRs.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns remain that another, more pathogenic SARS-CoV-2 variant will become dominant or that another new pathogenic virus will circulate in the near future for which large-scale (booster) vaccinations will be necessary. An important lesson we can learn from this study is that, in that case, the aim of vaccination should be to reach an antibody level as high as possible to prevent infection and severe disease in this vulnerable patient group and not just reaching seropositivity, as is emphasized in most current studies [ 31 , 32 , 49 , 50 ]. For future vaccinations, it should therefore be considered that KTRs do not follow the routine national vaccination programs, but a personalized vaccination scheme instead, based on antibody levels measured at a set time after vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Rodríguez-Cubillo et al (111) also reported that compared with unvaccinated KTRs, vaccinated KTRs with at least low antibody titers (>20 AU/mL) exhibited improved outcomes in relation to pneumonia and mortality rates. Furthermore, patients with antibody titers >100 AU/mL had even better outcomes compared with those with lower antibody titers.…”
Section: Effects Of the Third Vaccine On Protection Against Omicron I...mentioning
confidence: 98%
“…Despite the less robust response in SOTRs than the general population, evidence has shown that vaccination still provides significant protection for SOTRs and reduced mortality, in the context of evolving COVID variants [ 19 , 20 , 21 ]. Antibodies produced by COVID-19 vaccination have demonstrated associations with the pneumonia severity and mortality in renal transplant recipients during the Omicron wave; even with lower titers than in the non-immunocompromised patient population, outcomes are better than in the unvaccinated population and are the best in those who achieved an antibody concentration of >100 AU/mL [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%